Impact of COVID-19 on Travelling Behaviour of Nepalese Domestic Tourists - Sunita Dabadi; Anisha Nagarkoti (ASEAN Multidisciplinary Research Journal, 2021)
The purpose of the current research was to obtain a comprehensive insight about impact of COVID-19 on travelling behaviour of Nepalese domestic tourists. The paper examines perspectives of domestic tourists and experiences of tourism industry experts to cover all the aspects that is important while obtaining the travelling behaviour trends of tourists. Furthermore, the study aims to analyse how operators are advancing in response to these consumer behaviours. The report primarily based on a qualitative approach considering that it aims at understanding the underlying factors influencing the domestic tourist’s behaviour to travel during the pandemic. An unstructured questionnaire was used for primary data collection from both interview and focus group discussions. The research revealed that the domestic tourists although are concerned about safety and security, they have realized the need for relaxation and break. Accessibility, unique destinations and strictness in following protocols are equally important requirement for all tourists. The decisions of domestic tourists according to the research demonstrates to be influenced tremendously by family factors, economic factors, personal preferences and situational factors especially brought out of the crisis. Social media and online presence play integral role in prompting individuals in every way of travelling. Although exceptional tourism service providers are offering discounts and promoting new type of packages, they seem to be lacking value added propositions, information marketing and operational competencies. Thus, resourceful recommendations based on worldwide practices and provisions for furthering the effort of all concerned authorities and service providers are developed which includes: marketing research to discover change in involvements brought by pandemic, appropriate operational practices and proactive promoting approaches.